Dysfunctional governance remains serious problem - The Financial Express (The Financial Express, 2014)
BRAC Institute of Governance and Development (BIGD), in association with Effective States and Inclusive Development (EISD), International Growth Centre and Think Tank Initiative, organised the three-day international conference on the political economy, accountability and governance.